The Role of Streptococcal Cell-Envelope Proteases in Bacterial Evasion of the Innate Immune System - Sophie McKenna; Kristin Krohn Huse; Sean Giblin; Max Pearson; Mohammed Said Majid Al Shibar; Shiranee Sriskandan; Stephen Matthews; James Edward Pease (Karger Publishers, 2021)
Bacteria possess the ability to evolve varied and ingenious strategies to outwit the host immune system, instigating an evolutionary arms race. Proteases are amongst the many weapons employed by bacteria, which specifically cleave and neutralize key signalling molecules required for a coordinated immune response. In this article, we focus on a family of S8 subtilisin-like serine proteases expressed as cell-envelope proteases (CEPs) by group A and group B streptococci. Two of these proteases known as Streptococcus pyogenes CEP (SpyCEP) and C5a peptidase cleave the chemokine CXCL8 and the complement fragment C5a, respectively. Both CXCL8 and C5a are potent neutrophil-recruiting chemokines, and by neutralizing their activity, streptococci evade a key defence mechanism of innate immunity. We review the mechanisms by which CXCL8 and C5a recruit neutrophils and the characterization of SpyCEP and C5a peptidase, including both in vitro and in vivo studies. Recently described structural insights into the function of this CEP family are also discussed. We conclude by examining the progress of prototypic vaccines incorporating SpyCEP and C5a peptidase in their preparation. Since streptococci-producing SpyCEP and C5a peptidase are responsible for a considerable global disease burden, targeting these proteases by vaccination strategies or by small-molecule antagonists should provide protection from and promote the resolution of streptococcal infections.